2019
DOI: 10.1080/11356405.2019.1630955
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and interpretation of teachers’ attitudes towards students with disabilities / Evaluación e interpretación de la actitud del profesorado hacia alumnos con discapacidad

Abstract: The process of including students with disabilities is necessarily influenced by teachers' attitudes towards them and towards their inclusion in education. After detecting the need to study the attitudes present in preschool and primary and secondary school teachers, this study was proposed as it was decided that an analysis of such attitudes could help to develop a better understanding of the current needs of the education system. This study analysed data on attitudes from a total of 175 teachers (29.10% male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 28 publications
(124 reference statements)
4
18
0
13
Order By: Relevance
“…Of the eighteen studies that analyzed the influence of gender, seven found that women tend to be more positive [20][21][22][23][24][25][26] and four found that men have better attitudes [27][28][29][30].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the eighteen studies that analyzed the influence of gender, seven found that women tend to be more positive [20][21][22][23][24][25][26] and four found that men have better attitudes [27][28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding teaching experience, 10 studies analyzed its influence (see Tables 1 and 4): three found that teaching experience has a positive correlation with positive attitudes toward inclusion [27,28,31], three found the opposite [26,29,32], and the rest did not find a statistically significant relation [33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the a posteriori analysis (Scheffé test) showed a higher use of measures to attend to diversity in teachers with less experience, a doctorate degree, and who developed their work in provinces with a low number of inhabitants. In that sense, it is important to highlight the importance of beliefs and attitudes that teachers had on diversity, which is not put into practice for the inclusive educational activities in Secondary Education Schools [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Intellectual disability in mentally retarded students makes it hampered in activities, including when studying [13]. According to the American Psychiatric Association (APA) [14], Mental retardation is classified into four: first, mild (IQ <70) in this category students are able to be educated, trained and can take care of themselves, secondly, moderate (IQ 35-50), students can be educated and trained but physical abnormalities have emerged as innate, third, Severe (IQ 20-35), students need guarding because they cannot take care of themselves, fourth, profound (IQ> 20) has serious disabilities, both physical and intelligence.…”
Section: Introductionmentioning
confidence: 99%